The Legality of the Provision of Remission to Military Prisoners in Accordance with the Equality Before the Law Principle - Wulandari, Endah (Dinasti International Journal of Digital Business Management, 2025)
The Provision of Remissions to Napimil (Military Prisoner) at Lemasmil (Military Penitentiary Institution) is an effort to integrate social reintegration so that soldiers who have the TNI identity are guided by the Soldier's Code of Ethics and / or Officer Code of Ethics, are aware of their mistakes, improve themselves, and do not repeat criminal acts so that they can be accepted and returned to its unit in accordance with the provisions of laws and regulations. Thus, granting remissions to Napimil at Lemasmil is an effort to social reintegration of Napimil, so it needs to be regulated with a clear and straight regulations, in relation to the authority of the TNI Commander in granting Remission requests. The granting of authority to the TNI Commander can only be done if the Military Correctional Law has been issued. Given the importance of structuring the military correctional system, including the provision of remissions for Napimil, it is necessary to support the various competent parties to encourage the Military Correctional Bill to become a priority so that it can be immediately passed along with its derivative regulations.